The Effect of Young Green Coconut (Cocos nucifera L. var. viridis) Water on Dysmenorrhea in Adolescent Girls - Maifita, Yesi; Armalini, Rika; Nisa, Setia; Andriani, Linda (Journal of Health and Nutrition Research, 2025)
Dysmenorrhea, or menstrual pain, is a prevalent condition among adolescent girls. Various strategies have been employed to alleviate dysmenorrhea, one of which is the consumption of young coconut water, which is known for its rich electrolyte and mineral content. This study aimed to examine the effect of young coconut water consumption on the intensity of menstrual pain among adolescent girls. A pre-post experimental study design with a one-group pre-test–post-test approach was employed. The study was conducted at SMPN 39 Padang, a junior high school located in West Sumatra, Indonesia, and involved 189 female students from grades VII, VIII, and IX. A purposive sample of 12 students who reported experiencing dysmenorrhea was selected for the intervention. Participants were instructed to consume young coconut water for three consecutive days during menstruation. The intensity of menstrual pain was assessed using the Numeric Rating Scale (NRS) before and after the intervention. Data analysis was conducted using paired t-tests. Univariate analysis demonstrated a reduction in mean pain scores from 4.00 ± 1.35 (indicating moderate pain) to 1.58 ± 0.67 (indicating mild pain). The paired t-test revealed a statistically significant decrease in menstrual pain intensity following the intervention (p-value = 0.000, p < 0.05). In conclusion, the consumption of young coconut water was found to be effective in reducing the intensity of dysmenorrhea among adolescent girls. It may serve as a safe, natural, and accessible complementary approach for managing dysmenorrhea in adolescents